Nursing care management strategies to address the COVID-19 pandemic - Gabriela Marcellino de Melo Lanzoni; Leonardo Pereira de Sousa; Viviane Pecini da Cunha; Ana Lúcia Schaefer Ferreira de Mello; Alexandre Pazetto Balsanelli; José Luís Guedes dos Santos (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To characterize nursing care management strategies for addressing the COVID-19 pandemic. Method: A descriptive, qualitative study conducted with 22 nurse professionals at a University Hospital in Southern Brazil. Data collection through interviews in June and August 2021, analyzed according to Bardin’s Content Analysis and the theoretical framework of complex thinking. Results: The identified strategies were organized into four categories: Reorganization of health services; People management and emergency admission; Multiprofessional articulation; and Bedside nursing care. Final Considerations: Professional performance revealed a complex interplay between leadership and care management practices, even in the face of working condition restrictions, and were understood as crucial in the pandemic scenario.